Optimal Scheduling of Bevacizumab and Pemetrexed/Cisplatin Dosing in Non‐Small Cell Lung Cancer. (9th May 2019) - Schneider, Benjamin K.; Boyer, Arnaud; Ciccolini, Joseph; Barlesi, Fabrice; Wang, Kenneth; Benzekry, Sebastien; Mochel, Jonathan P.
Abstract : Bevacizumab‐pemetrexed/cisplatin (BEV‐PEM/CIS) is a first‐line therapeutic for advanced nonsquamous non‐small cell lung cancer. Bevacizumab potentiates PEM/CIS cytotoxicity by inducing transient tumor vasculature normalization. BEV‐PEM/CIS has a narrow therapeutic window. Therefore, it is an attractive target for administration schedule optimization. The present study leverages our previous work on BEV‐PEM/CIS pharmacodynamic modeling in non‐small cell lung cancer–bearing mice to estimate the optimal gap in the scheduling of sequential BEV‐PEM/CIS. We predicted the optimal gap in BEV‐PEM/CIS dosing to be 2.0 days in mice and 1.2 days in humans. Our simulations suggest that the efficacy loss in scheduling BEV‐PEM/CIS at too great of a gap is much less than the efficacy loss in scheduling BEV‐PEM/CIS at too short of a gap.